KEFEKTIFAN MODEL DIRECT LEARNING TERHADAP KEMAMPUAN MENULIS CERPEN MTS MAMBAUL HISAN - Hamidah; Wardiah, Dessy; Murniviyanti, Liza (Parataksis: Jurnal Bahasa, Sastra, dan Pembelajaran Bahasa Indonesia, 2022)
This study is entitled The Effectiveness of Direct Learning Model on the Ability to Write Short Stories for Class VIII Students MTS Mambaul Hisan Sungai Lilin (Candle River). The formulation of this research problem is "Is the direct learning model effective for the ability to write short stories for grade VIII MTs Mambaul Hisan Sungai Lilin". This study aims to determine the effectiveness of the direct learning model on the ability to write short stories for grade VIII MTs Mambaul Hisan Sungai Lilin students. This research is a research with a quantitative descriptive approach using a compeletely randomized design in the form of Pre-Experiment using One Group Pretest Postest Design. The population of this study was all grade VIII students at MTs Mambaul Hisan Sungai Lilin. The research sample uses Cluster Random Sampling so that a sample class is obtained namely class VIII 3. Data collection techniques use observation, tests, and documentation. Data analysis techniques using non-parametric statistical tests, namely the Wilcoxon test, obtained the results that z calculate < ztabel (0.071 < 0.4721), then Ho was rejected or H1 was accepted so that it can be concluded that the direct learning model is effective for improving students' short story writing skills in class VIII MTs Mambaul Sungai Lilin.